Earthen construction: structural vulnerabilities and retrofit solutions for seismic actions - Oliveira, C. F. (2013)
Earthen structures present very appealing characteristics regarding a more sustainable practice with the preservation of our natural resources. However, when subjected to earthquake ground motions, this type of construction may present a deficient performance, which may cause significant human losses and important structural damage. The seismic response of earthen structures is typically characterized by fragile failures. There are several examples of recent earthquakes that affected earthen buildings in a severe way, evidencing the vulnerability of this type of construction, like the El Salvador earthquake, in 2001, the Bam, Iran earthquake, in 2003, the Pisco, Peru earthquake, in 2007 and the Maule, Chile earthquake, in 2010. The construction of earth structures on earthquake-prone areas must be carefully studied and should include seismic reinforcement solutions in order to improve their seismic performance. In this paper, the performance of earthen structures in recent earthquakes will be examined, analyzing failure modes inherent to these particular construction materials and associated construction techniques. Also, seismic reinforcement approaches and techniques will be presented in a comprehensive manner. Examples of tests conducted for the assessment of retrofitting solutions efficiency will be presented, and the results obtained will be discussed.